Business process change : - Harmon, Paul (Morgan Kaufmann Publishers, 2003)
This book is a must-read for every business manager who wants to manage business process change in an e-business environment; it's a true practitioner's guidebook to the complex world of end-to-end business process management. The book not only gives an excellent introduction to all aspects of process change management (from analysis or redesign to implementation to monitoring to improvement of business processes), but also provides a comprehensive guide to state-of-the-art techniques and technologies supporting the various aspects of this process (from process design methodologies to realizing business processes via choreography of Web services).